Effect of Surfactants and Cosurfactants on the Characteristics of Mangosteen Rind Extract Hand Body Lotion - Eni Masruriati; Khofifah Wijayanti (Indonesian Journal of Global Health Research, 2024)
The surfactants and co-surfactants combination in nanoemulsion formulations is important to obtain optimal formulations. Mangosteen rind extract has various benefits. Objective: determine the effect of a combination of surfactant (Tween 80) and Co surfactant (PEG 400) on the physical characteristics of mangosteen rind extract nanoemulsion. The research method was carried out by comparing the physical characteristics of the nanoemulsion formula of mangosteen rind extract by testing pH, viscosity and particle diameter. Three formulas were made (F1, F2 and F3) and one formula without co-surfactant as a negative control (KN). The combination of surfactant and cosurfactant provided pH, viscosity and particle diameter characteristics that were significantly different between formulas and with the negative control. The combination of surfactants and co-surfactants influences the properties of Mangosteen Rind Extract (Garcinia mangostana L) Hand and Body Lotion.